PROSPECTS FOR DEVELOPING WOMEN’S POLITICAL RESPONSIBILITY IN THE IMPLEMENTATION OF UZBEKISTAN’S NEW DEVELOPMENT STRATEGY - Juraboyeva, Dilmura (International Conference on Linguistics & Translation, 2026)
This article analyzes the prospects for developing women’s political responsibility within the framework of implementing Uzbekistan’s new development strategy. It examines the increasing role of women in political decision-making processes, public administration, and civic engagement in the context of ongoing democratic reforms. The study highlights institutional, legal, and socio-cultural factors that influence women’s political participation and responsibility, and evaluates current policies aimed at strengthening gender equality and enhancing women’s leadership potential. The article concludes that fostering women’s political responsibility is an essential component of sustainable development and democratic transformation in contemporary Uzbekistan.